2022
DOI: 10.1093/ofid/ofac678
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Race Disparities in Mortality and Years of Potential Life Lost Among People With HIV: A 21-Year Observational Cohort Study

Abstract: Background Since the availability of antiretroviral therapy, mortality rates among people with HIV (PWH) have decreased; however, this does not quantify premature deaths among PWH, and disparities persist. Methods We examined all-cause and premature mortality among PWH receiving care at the Vanderbilt Comprehensive Care Clinic from January 1998 – December 2018. Mortality rates were compared by demographic and clinical factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…estimates of non-HIV-related mortality among PWH. We found that this effect was more substantial among female individuals than male individuals with HIV, given the demographics of female individuals at highest risk for HIV acquisition [55][56][57], resulting in a lower modelprojected lifetime AAD cumulative incidence among female individuals with diagnosed HIV compared with female individuals in the general population.…”
Section: Lifetime Cumulative Incidence Of Aad (%)mentioning
confidence: 99%
“…estimates of non-HIV-related mortality among PWH. We found that this effect was more substantial among female individuals than male individuals with HIV, given the demographics of female individuals at highest risk for HIV acquisition [55][56][57], resulting in a lower modelprojected lifetime AAD cumulative incidence among female individuals with diagnosed HIV compared with female individuals in the general population.…”
Section: Lifetime Cumulative Incidence Of Aad (%)mentioning
confidence: 99%
“…People with long-standing exposure to both HIV and antiretroviral therapy (ART) are at a significantly increased risk of developing cardiovascular disease and cardiac dysfunction [1,2]. However, no robust options are currently available for identifying which persons with HIV (PWH) are at the highest risk of future cardiovascular disease [3,4]. We, therefore, performed proteomic profiling in biospecimens from children and young adults with HIV without clinical cardiac disease, comparing those with and without evidence of subclinical cardiac dysfunction, as evidenced by an abnormal myocardial performance index (MPI).…”
Section: Introductionmentioning
confidence: 99%
“…Social and structural determinants of health place Black women at higher risk for adverse HIV treatment outcomes. For example, only 62% of Black women are estimated to have achieved sustained viral suppression (compared with 70% of white women) [2] and Black women are more likely to die prematurely because of HIV compared with both men and women of any race or ethnicity [3]. Recognizing this inequity, the National HIV/ AIDS Strategy (NHAS) 2022-2025 identified cis-gender Black women as a priority population for HIV prevention and treatment efforts.…”
mentioning
confidence: 99%